2018
DOI: 10.1089/scd.2018.0056
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Autologous Endometrial Mesenchymal Stromal Cells After Application in the Healthy Equine Uterus

Abstract: Because of their distinct differentiation, immunomodulatory, and migratory capacities, endometrial mesenchymal stromal cells (MSCs) may provide an optimum source of therapeutic cells not only in relation to the uterus but also for regeneration of other tissues. This study reports the fate of endometrial MSCs following intrauterine application in mares. Stromal cell fractions were isolated from endometrial biopsies taken from seven reproductively healthy mares, expanded, and fluorescence labeled in culture. Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…The identification of novel MSC sources has also represented a step forward in that regard. For example, although BM and AT are well-established sources of clinical MSCs in both humans and animals, EM is now emerging as a promising alternative source with defined cell differentiation and immunomodulatory properties [ 23 , 24 , 30 , 33 ]. It is thus critical to compare the immunomodulatory properties of MSCs across different tissues to identify the most optimal source(s) for particular clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of novel MSC sources has also represented a step forward in that regard. For example, although BM and AT are well-established sources of clinical MSCs in both humans and animals, EM is now emerging as a promising alternative source with defined cell differentiation and immunomodulatory properties [ 23 , 24 , 30 , 33 ]. It is thus critical to compare the immunomodulatory properties of MSCs across different tissues to identify the most optimal source(s) for particular clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…A report found that MSC administration decreases neutrophil numbers and increases anti-inflammatory ILRN expression in the endometrium of the normal mare [342]. Interestingly, while one study found that MSCs also attenuate markers of uterine inflammation following treatment, cells were unable to penetrate the endometrium and remained within the uterine lumen [343]. However, another study reported that intrauterine infusion of MSCs effectively engrafted MSCs in periglandular spaces [344].…”
Section: Stem Cellsmentioning
confidence: 99%
“…In horses, the vast majority of reports on the medical use of MSCs are for the treatment of injuries of skeletal muscle, cartilages, and ligaments, which are the main causes of reduced performance in equine athletes, leading to important health and economic issues [ 36 ]. MSCs have also been used in mares with endometrial diseases [ 37 , 38 ]. The underlying cause of all these pathologies is inflammation, of which PGE2 is a key mediator.…”
Section: Discussionmentioning
confidence: 99%
“…The herein reported transduction efficiency and cell recovery did not greatly differ from other MSC reports. Nevertheless, using FACS separation yields a comparative benefit for selection compared to other methods, such as limiting dilution, which is time consuming, of low throughput, and does not necessarily guarantee clonality [ 37 ], nor antibiotic selection [ 38 ], which could impair cell growth after editing.…”
Section: Discussionmentioning
confidence: 99%